Image acquisition and preprocessing for machine vision systems - Sinha, P. K. 1947- (SPIE, 2012)
Image Acquisition and Pre-Processing for Machine Vision Systems provides a unique combination of the operational details of imaging hardware and analytical theories of low-level image processing functions. By a skilful blend of optics, stage lighting, and framegrabber descriptions, and detailed theories of CCD and CMOS image sensors, image formation, and camera calibration, the image acquisition part of the book provides a comprehensive reference text for image acquisition. The pre-processing part brings together a wide range of enhancement and filtering kernels and imaging functions through well-structured analytical bases. With unified coverage of image acquisition modules and pre-processing functions, this book bridges the gaps between hardware and software on one hand and theory and applications on the other. With its detailed coverage of imaging hardware and derivations of pre-processing kernels, it is a useful design reference for students, researchers, application and product engineers, and systems integrators.
"SPIE Digital Library."--Website.
Keywords: Computer vision.; Identification.; Electronic data processing -- Data preparation.; elektronické knihy; electronic books